Pendidikan Kristen dalam Pelayanan Konseling Pranikah di Era Disrupsi - Carolina Etnasari Anjaya; Andreas Fernando; Wahju Astjarjo Rini (Jurnal Teologi Berita Hidup, 2022)
The era of disruption encourages all humans to adapt to the changes that occur. Christian youth and Christian families are required to be able to withstand these changes by living in the firmness of the Christian faith, according to God's will. Christian education in premarital counseling is very important in this era because through it Christian families will be able to survive in an increasingly uncertain world. This research method is descriptive qualitative, with literature study and observation techniques. The author uses the Bible and various relevant literature. The purpose of this study is to provide a description of how Christian education can form premarital counseling that can guide Christian families in this era. The results of the study conclude that it is necessary to transform premarital counseling from just a church service program to Christian education to provide a new form. Christian education in pre-marital counseling is developed to post-marital counseling, which is carried out continuously throughout life according to the principles of Christian education. The implementation of Christian education in pre-marital counseling is as follows: First, the teaching materials emphasize the development of the personal dimension as a creation that is in the image and likeness of God and the relational dimension, building a relationship that is holy and pleasing to God. Second, the implementation of Christian education in pre-marital counseling includes six stages: First, the preparation of young people to find a life partner. Two, at a time when a future husband and wife decided to start a new family. Three, the young family stage. Four, pre-adolescent and adolescent family stages. Five, the family stage of adulthood, when the children in the family have started to grow up. Six, the stages of old age. Third, forming counselors as guides and guides who fear God, living the truth of God's word so that they can become examples of life.  Era disrupsi mendorong semua manusia untuk beradaptasi dalam perubahan yang terjadi. Orang muda Kristen dan keluarga Kristen dituntut untuk dapat bertahan menghadapi perubahan tersebut dengan tetap hidup dalam kekokohan iman Kristen, sesuai kehendak Allah. Pendidikan Kristen dalam konseling pranikah menjadi sesuatu hal yang sangat penting di era ini karena melaluinya  keluarga Kristen akan mampu bertahan di dalam dunia yang semakin penuh ketidakpastian.  Metode  penelitian ini adalah kualitatif deskriptif, dengan teknik studi pustaka dan observasi. Penulis mempergunakan Alkitab dan berbagai literatur yang relevan. Tujuan dari penelitian ini adalah memberikan deskripsi mengenai  bagaimana pendidikan Kristen dapat membentuk konseling pranikah dapat menjadi penuntun keluarga Kristen di era ini. Hasil penelitian menyimpulkan bahwa perlu transformasi konseling pranikah dari sekadar program pelayanan gereja menjadi pendidikan Kristen untuk memberikan bentukan baru. Pendidikan Kristen dalam konseling pranikah dikembangkan sampai pada konseling paska menikah, diselenggarakan secara terus menerus berkesinambungan sepanjang hayat memenuhi prinsip pendidikan Kristen. Implementasi pendidikan Kristen dalam konseling pranikah sebagai berikut: Pertama, materi pengajaran menekankan kepada  pengembangan dimensi personal sebagai ciptaan yang segambar dan serupa Tuhan dan dimensi relasional, membangun hubungan yang kudus dan berkenan bagi Tuhan.  Kedua, Penyelenggaraan  pendidikan Kristen dalam konseling pra nikah  meliputi enam tahap: Satu, persiapan kaum muda mencari pasangan hidup. Dua,  pada masa ketika sepasang calon suami istri memutuskan untuk membina keluarga baru. Tiga, tahap keluarga usia muda. Empat, tahapan keluarga pra remaja dan remaja. Lima, tahapan keluarga masa dewasa, ketika anak-anak dalam keluarga sudah mulai tumbuh dewasa. Enam, tahapan masa tua.  Ketiga, membentuk konselor sebagai  pembimbing dan penuntun yang takut akan Tuhan, menghidupi kebenaran firman Tuhan sehingga mampu menjadi teladan hidup.